2020
DOI: 10.1101/cshperspect.a039669
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Opioid Withdrawal Syndrome (NOWS): A Transgenerational Echo of the Opioid Crisis

Abstract: The incidence of neonatal opioid withdrawal syndrome (NOWS) has increased substantially in the setting of the opioid epidemic, a major public health problem in the United States. At present, NOWS has commonly used assessment and treatment protocols, but new protocols have questioned old practices. However, because of limited access to opioid use disorder (OUD) treatment and socioeconomic factors, many pregnant (and postpartum) women with OUD do not receive treatment. The pathophysiology of NOWS is not complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 77 publications
1
26
0
Order By: Relevance
“…The impacts of opioid use on children occur both through prenatal exposure of infants to opioids and through the effects of opioid use and addiction on the mother’s ability to parent. Neonatal abstinence syndrome (NAS), which occurs when infants are exposed to opioids that cross the placental barrier during pregnancy, causes direct neurological impacts but also can disrupt caregiving through symptoms (e.g., high-pitched cry, irritability, difficulty sleeping and soothing) 14 which may make it more difficult for mothers to read their infants’ cues and persist in providing nurturance when infants are distressed. Medication assisted treatment (MAT) is the gold-standard treatment option for pregnant women with opioid use disorder.…”
Section: The Unique Challenge Of Maternal Opioid Usementioning
confidence: 99%
“…The impacts of opioid use on children occur both through prenatal exposure of infants to opioids and through the effects of opioid use and addiction on the mother’s ability to parent. Neonatal abstinence syndrome (NAS), which occurs when infants are exposed to opioids that cross the placental barrier during pregnancy, causes direct neurological impacts but also can disrupt caregiving through symptoms (e.g., high-pitched cry, irritability, difficulty sleeping and soothing) 14 which may make it more difficult for mothers to read their infants’ cues and persist in providing nurturance when infants are distressed. Medication assisted treatment (MAT) is the gold-standard treatment option for pregnant women with opioid use disorder.…”
Section: The Unique Challenge Of Maternal Opioid Usementioning
confidence: 99%
“…Characteristic manifestations of NOWS include decreased body weight, high-pitched crying, irritability, tremors, and an inability to be soothed, among many others (Piccotti et al, 2019; Weller, Crist, Reiner, Doyle, & Berrettini, 2020). Reviews and meta-analyses of clinical data have reported infant-adolescent outcomes associated with in utero opioid exposure, including lower scores in neurocognitive and developmental assessments, decreased motor skills, and increased hyperactivity and aggression (Maguire et al, 2016; Minnes, Lang, & Singer, 2011; Nygaard, Slinning, Moe, & Walhovd, 2017; Weller et al, 2020; Yeoh et al, 2019). However, other studies report variability in outcomes among children exposed prenatally to opioids, leading to potential differences in vulnerability and resiliency in these individuals (Labella, Eiden, Tabachnick, Sellers, & Dozier, 2021; Sarfi, Eikemo, Welle-Strand, Muller, & Lehmann, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A study of maternal-infant dyads prenatally exposed to opioids reported that roughly 30-60% of newborns were diagnosed with NOWS (Leyenaar et al, 2021; Skumlien, Ibsen, Kesmodel, & Nygaard, 2020), which suggests that a proportion of newborns exposed to opioids in utero may develop a phenotype severe enough to require pharmacological and/or non-pharmacological interventions. Characteristic manifestations of NOWS include decreased body weight, high-pitched crying, irritability, tremors, and an inability to be soothed, among many others (Piccotti et al, 2019; Weller, Crist, Reiner, Doyle, & Berrettini, 2020). Reviews and meta-analyses of clinical data have reported infant-adolescent outcomes associated with in utero opioid exposure, including lower scores in neurocognitive and developmental assessments, decreased motor skills, and increased hyperactivity and aggression (Maguire et al, 2016; Minnes, Lang, & Singer, 2011; Nygaard, Slinning, Moe, & Walhovd, 2017; Weller et al, 2020; Yeoh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal abstinence syndrome (NAS) occurs in a significant proportion of newborns exposed to substances in utero. More recently, the term neonatal opioid withdrawal syndrome (NOWS) has been introduced, but the term NAS is still used for cases of polysubstance exposure [ 1 ]. In Canada, maternal opiate use in pregnancy has been steadily rising resulting in as many as 1850 newborns born with NAS per year [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%